PENGARUH WORK FAMILY CONFLICT DAN FLEKSIBILITAS KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Bagian Pengadaan Barang dan Jasa Sekretariat Daerah Kabupaten Bondowoso) - K Karjono; Ni Nyoman Putu Martin; Mohammad Thamrin (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The aim of this research is to determine and analyze the influence of work family conflict and work flexibility on the performance of employees of the Goods and Services Procurement Section of the Bondowoso Regency Regional Secretariat. The number of samples for this study was 126. The analysis technique used was Structural Equation Model (SEM) using WarpPLS 7.0. The results of data analysis show that the variables work family conflict, work motivation and work flexibility partially have a significant effect on the performance of employees in the Goods and Services Procurement Section of the Regional Secretariat of Bondowoso Regency